Prevalencia de Parásitos intestinales en 100 pollos de línea Broiler Cobb 500 en el Recinto Santo Thomas de la parroquia Ricaurte - Silva Toala, Wendy Maoly (2023)
Intestinal parasites in birds are organisms that reside within the various segments of the digestive system and have the ability to obtain nutrients at the expense of the host. An intestinal parasite infestation in Cobb 500 broilers refers to the presence and proliferation of parasitic organisms. In the intestinal tract of this specific breed of chicken raised for meat production. The present work was carried out in the Santo Thomas Campus of the Ricaurte parish, with the objective of determining the prevalence of intestinal parasite load in 100 Broiler Cobb 500 line chickens, in which it consisted of carrying out coproparasitic examinations, therefore, It was determined that 100% of the coproparasitic analyzes carried out in the laboratory of the Technical University of Babahoyo there was an absence of intestinal parasite eggs, due to the results obtained, it was determined that there are no risk factors during the growth and development in chickens of the Broiler Cobb 500 line, however, these results will depend on the factors of hygiene and care in the feeding of each hatchery, which in this case study were optimal in the breeding carried out in the Santo Thomas Campus of the Ricaurte parish. It is important to remember that each situation can be unique and that the interaction of several factors can influence the appearance of parasitic problems when raising Broiler Cobb 500 chickens.